2012
DOI: 10.1088/0004-637x/748/1/44
|View full text |Cite
|
Sign up to set email alerts
|

GRB 071112c: A Case Study of Different Mechanisms in X-Ray and Optical Temporal Evolution

Abstract: We present a study on GRB 071112C X-ray and optical light curves. In these two wavelength ranges, we have found different temporal properties. The R-band light curve showed an initial rise followed by a single power-law decay, while the X-ray light curve was described by a single power-law decay plus a flare-like feature. Our analysis shows that the observed temporal evolution cannot be described by the external shock model in which the X-ray and optical emission are produced by the same emission mechanism. No… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…A less intense flare was observed in the GRB 071112C X-ray afterglow. The fact that no corresponding flare was detected in the optical was used by Huang et al (2012) to argue that different mechanisms were responsible for the time evolution of the X-ray and optical afterglows. The simple power-law structure of the optical light curve was shown to be consistent with the external shock model, whereas late injection and internal shocks inside the jet itself were invoked to explain the excess X-ray emission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A less intense flare was observed in the GRB 071112C X-ray afterglow. The fact that no corresponding flare was detected in the optical was used by Huang et al (2012) to argue that different mechanisms were responsible for the time evolution of the X-ray and optical afterglows. The simple power-law structure of the optical light curve was shown to be consistent with the external shock model, whereas late injection and internal shocks inside the jet itself were invoked to explain the excess X-ray emission.…”
Section: Discussionmentioning
confidence: 99%
“…et al 2011), GRB 071112C (Huang et al 2012), GRB 050502B (Falcone et al 2006), GRB 060607A (Ziaeepour et al 2008), and GRB 050421 (Godet et al 2006). It is generally accepted that these flares are a product of late-time injections of energy into the system by the GRB's central engine, but this is not the only possible scenario.…”
Section: Introductionmentioning
confidence: 99%
“…We used light curves published by Wiersema et al (2012) and Filgas et al (2011) for GRBs 091018 and 091127, respectively. For GRB 071112C, the joint data sets of Huang et al (2012) and Covino et al (2013) were used.…”
Section: Flux Calibration Verificationmentioning
confidence: 99%
“…The onset process were reported in some bursts (e.g., Molinari et al, 2007;Huang et al, 2012) , thanks to the fast slew capability of Swif t satellite and quick multi-wavelength follow-up observations by ground-based telescopes. In those reports, other radiations from reverse shock or internal shock or others were detected in optical or X-ray light curves.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the variation in the optical light curve of GRB 060607 (Molinari et al, 2007) at the later phase was detected. During X-ray observations, flares (e.g., Burrows et al, 2005) or emission in steep decay phase which is related with internal-shock process were detected (e.g., Zhang 2007;Huang et al, 2012). Recently, Li et al,(2015) found that in 87 well sampled and simultaneously observed GRBs, only 9 GRBs match the prediction of the standard fireball model, and have a single power law decay in both energy bands during their entire observations.…”
Section: Introductionmentioning
confidence: 99%